Dampak Pendayagunaan Infaq Produktif Terhadap Peningkatan Pendapatan Pada Mustahiq YDSF (Yayasan Dana Sosial Al-Falah) di Kediri - Haryanto, Chandra Ari; Laila, Nisful (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The impact of infaq productive utilization of the increased income on mustahiq YDSF (Foundation of Social Funds Al-Falah) in Kediri. The goal of this research is to know the impact of utilization of infaq productive done by mustahiq to increase revenues.The research method used is a qualitative approach, strategy case studies andanalysis techniques, descriptive data collection is done through interviews and observations of the informants. Informants were participants KUM (Independent Business Group) in Kediri composed of 8 people who have attended this program and get help infaq in the from the board LAZ YDSF (the foundation of social funds al-falah) through KUM.Result from this study that the productive utilization of infaq by mustahiq through KUM (Independent business group) in the form of venture capital has an impact on income growth mustahiq. Can be seen that the eight mustahiq interviewed seven mustahiq who experienced improvement, where as only one mustahiq whose income is not increasing.